2019
DOI: 10.1186/s12958-019-0522-7
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates gestational diabetes mellitus via targeting NLRP3 inflammasome in genetic mice

Abstract: Background As the most ordinary metabolic disorder during pregnancy, gestational diabetes mellitus (GDM) has become a severe risk for the health of both pregnant female and fetus. Astragaloside IV (AS-IV) is the dominant active component in Astragalus membranaceus. It has been proved that AS-IV has anti-inflammation and immune-regulation function. We aimed to demonstrate the function of AS-IV in the therapy of GDM and the molecular mechanism in this process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In vitro analysis of the mechanism underlying the switch of macrophages from anti-inflammatory M2 to pro-inflammatory M1 phenotype have shown that under high glucose conditions the phagocytosis of apoptotic β-cells causes macrophages switch from M2 to M1 phenotype, correlating with the activation of the NLRP3-inflammasome that triggers IL-1β release and increases ROS production [68]. In agreement with a role for NLRP3-inflammasome and subsequent increase in IL-1β during GDM, the inhibition of the pancreatic NLRP3 inflammasome in a GDM mouse model resulted in improved glucose homeostasis [69]. Moreover, in vitro treatment of human and mouse islets with IL-1β, a cytokine that is increased in GDM [61], causes β-cell dedifferentiation and dampened insulin secretion capacity [66].…”
Section: Inflammation Underlying Gdm Development and Derived Adverse mentioning
confidence: 80%
“…In vitro analysis of the mechanism underlying the switch of macrophages from anti-inflammatory M2 to pro-inflammatory M1 phenotype have shown that under high glucose conditions the phagocytosis of apoptotic β-cells causes macrophages switch from M2 to M1 phenotype, correlating with the activation of the NLRP3-inflammasome that triggers IL-1β release and increases ROS production [68]. In agreement with a role for NLRP3-inflammasome and subsequent increase in IL-1β during GDM, the inhibition of the pancreatic NLRP3 inflammasome in a GDM mouse model resulted in improved glucose homeostasis [69]. Moreover, in vitro treatment of human and mouse islets with IL-1β, a cytokine that is increased in GDM [61], causes β-cell dedifferentiation and dampened insulin secretion capacity [66].…”
Section: Inflammation Underlying Gdm Development and Derived Adverse mentioning
confidence: 80%
“…AS-IV is the major active component of Astragalus membranaceus . Our group has studied AS-IV in the pathogenesis of many diseases for a long time, and discovered that AS-IV could effectively protect against GDM by inhibiting NLRP3 inflammasome in genetic GDM mice ( 13 ). Because of the multifunctional properties of AS-IV, we further investigated the protective effect of AS-IV against GDM and found that, AS-IV also attenuated hepatic gluconeogenesis to ameliorate GDM ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous publications have demonstrated that AS-IV could protect against diabetes and its complications, such as diabetic nephropathy, myocardial damage, diabetic wound healing and diabetic retinopathy ( 6 , 10 , 11 , 12 ). Our group has investigated the effect of AS-IV in GDM-related diseases and discovered that AS-IV could effectively ameliorate GDM in genetic mouse model of GDM by inhibiting NLRP3 inflammasome in the pancreas ( 13 ). We also found that AS-IV remarkably reduced hepatic gluconeogenesis, hepatic inflammation and oxidative stress to alleviate GDM in mice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glombik et al [ 113 ] observed that maternal diabetes causes the activation of NLRP3 inflammasome signaling by increasing the level of the NLRP3 protein subunit, and glyburide, as a NLRP3 inflammasome inhibitor, diminishes the level of NLRP3 protein and caspase-1 subunits, and has particular therapeutic value in anti- metabolic-related inflammation. Zhang et al [ 114 ] found that astragaloside IV (AS-IV) treatment was an effective therapy for GDM in a mouse model through the inhibition of NLRP3 inflammasome in the pancreas. Negi et al [ 115 ] reported allopurinol significantly inhibited NLRP3 activation, inhibited trophoblast secretion of inflammatory IL-1β; caspase-1 activity, reduced additional pro-inflammatory and anti-angiogenic responses to excess glucose, prevent placental dysfunction and adverse pregnancy outcomes in patients with GDM.…”
Section: Nlrp3 and Reproductive Disordersmentioning
confidence: 99%